Морфология говоров Терского берега Белого моря(Morphology of the Dialects of the Ter Coast of the White Sea) - Pineda, David (Poljarnyj vestnik, 2001)
The present article gives an overview of the morphological characteristics of the dialect of two villages on the Ter Coast of the Kola Peninsula, Varzuga and Umba. This topic has not previously been studied thoroughly. Features of this dialect are compared to those known in Arkhangelsk dialects. Salient details in the dialects of the two villages are: the common form for genitive, dative and prepositional cases of class II nouns: -y/-i; the use of the endings -ma/-my in the instrumental plural; the contraction of vowels in verbs and adjectives due to the loss of intervocalic [j]; the use of the postpositional particle -to/ta/ot. Some of the features are rare, for instance, present forms of verbs with a velar stem without the k/č and g/ž shifts (pečet-peket).